Experience with and attitude toward clozapine use among patients receiving clozapine on long term and their caregivers - Sandeep Grover; Chandrima Naskar; Subho Chakrabarti (Indian Journal of Psychiatry)
Background: Despite clozapine being the gold standard for treating patients suffering from treatment-resistant schizophrenia, the experience and attitude of patients receiving clozapine for a long duration and their caregivers have not been evaluated, especially in India and other low-middle-income countries. Also, no standardized scale has been validated for such assessment. Objective: This study aimed to evaluate the perception regarding clozapine among patients and their caregivers. We also attempted to evaluate the factor structure of the scale for such assessment. Methods: A total of 172 consenting patients who have been receiving clozapine for ≥1 year and their caregivers were evaluated on self-designed questionnaires (patient and caregiver versions containing 44 and 47 items, respectively) to assess various aspects of their experiences about clozapine use. Results: A majority (70–80%) of patients and caregivers reported improvement in psychotic symptoms, mood symptoms, and overall functioning with starting of clozapine. However, about 40% of the patients reported cognitive side effects, and 20–25% reported disabling side effects like lethargy, forgetfulness and decreased attention, and distress related to blood testing after starting of clozapine. Factor analysis of the questionnaires yielded five- and seven-factor models for the experience and attitude of the patients and the caregivers, respectively. The positive experiences were associated clinical and functional improvement, lower disability, and improvement in functioning as well as the self-reported perceived improvement by the patient and caregiver. Conclusion: This study suggests that patients tend to have an overall positive experience and attitude about using clozapine. The caregivers also report the beneficial effect on the caregiving. A good level of agreement was seen between the experience of patients, caregivers, and clinician-rated improvement in the psychopathology and functioning.